ANALISIS LAJU KOROSI PADA PLAT BESI MENGGUNAKAN EKSTRAK DAUN GAMAL (Gliricidia sepium) SEBAGAI INHIBITOR ALAMI DALAM MEDIA HCl 3% DAN H2O - Lapailaka, Titus; Anul, Olimpia Y. (Universitas Nusa Cendana, 2022)
Improving the corrosion resistance of iron in acidic environments is an important consideration in industry. This research was conducted to analyze the corrosion inhibition of iron using ethanolic extract of gamal leaf (Gliricidia sepium) as a natural inhibitor in 3% HCl and H2O media. The aim was to determine the effect of inhibitor concentration on the corrosion rate of iron plate immersed in corrosive media of 3% HCl and H2O and to determine the effect of immersion time on the efficiency of ethanolic extract of gamal leaf on the corrosion rate of iron plate in corrosive media of 3% HCl and H2O. The results indicated that the higher the concentration of ethanolic extract of gamal leaf, the lower the corrosion rate. The highest concentration of ethanolic extract of gamal leaf used was 10%, with the corrosion rate values of 0.0044 cm/year in 3% HCl media and 0.0051 cm/year in H2O media. It is observed that tanin compound in ethanolic extract of gamal leaf showed potential as an iron corrosion inhibitor in 3% HCl and H2O media with efficiencies of 91.46% and 88.19%, respectively.